Targeting complex, adaptive responses in melanoma therapy. (June 2020) - Cheng, Phil; Levesque, Mitchell Paul; Dummer, Reinhard; Mangana, Joanna
Highlights: Future targeted therapies require knowledge of complex adaptive drug responses. Drug combinations should target diverse mechanisms such as metabolism or signaling. Combined targeted/immune therapies show promise, but tolerability is problematic. Abstract: Our understanding of the complex, adaptive mechanisms of response to targeted therapies in metastatic melanoma is now leading to more effective combination treatments. These include the simultaneous inhibition of signalling pathways and metabolic programmes, as well as epigenetic mechanisms or immunological checkpoints. We review the latest pre-clinical and clinical results of strategies to delay tumor progression through combination approaches, and also highlight some of the problems ahead, including patient stratification, the complexity of targeting adaptive responses, and the management of more severe toxicities that result from double and triple-drug treatments.